2016
DOI: 10.20452/pamw.3479
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status in Poland

Abstract: functions of vitamin D seem to be higher (30-50 ng/ml; 75-125 nmol/l), 25 but still are considered uncertain. Some authors, however, argue that even for proper bone mineralization, levels higher than 30 ng/ml (75 nmol/l) are necessary. 26 Indisputably, low 25(OH)D levels (below 20 ng/ml) are common and were reported worldwide, 1-7 and this is a drawback because epidemiological data underlined an association between vitamin D deficit and a higher risk for chronic conditions and multimorbidity, including musculo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

15
102
5
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(141 citation statements)
references
References 21 publications
(33 reference statements)
15
102
5
7
Order By: Relevance
“…Thus, even if actual vitamin D deficiency was less common in their study population than indicated by Pludowski et al, 1 it is possible that substantial parts of the Polish population are vitamin D deficient or at high risk of deficiency.…”
mentioning
confidence: 59%
See 3 more Smart Citations
“…Thus, even if actual vitamin D deficiency was less common in their study population than indicated by Pludowski et al, 1 it is possible that substantial parts of the Polish population are vitamin D deficient or at high risk of deficiency.…”
mentioning
confidence: 59%
“…2-4 Thus, unless ongoing randomized trials 5 provide evidence for reduced risks of major chronic diseases at much higher 25(OH)D levels, the prevalence estimates for 25(OH)D levels below 25 or 30 nmol/l (deficiency) and 50 nmol/l (suboptimal, at risk of deficiency) presented by Pludowski et al 1 should be appreciated as their main findings with respect to public health implications.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, we did not study vitamin K levels reported to affect vascular calcifications in patients on hemodialysis 39 but not in nondialyzed patients. 40 As many healthy individuals 39 as well as dialyzed patients 41 are vitamin-D deficient, vitamin D should be supplemented first. As reported, correction of 25(OH)D deficiency in patients on hemodialysis was associated with better SHPT control with lower doses of vitamin D analogues.…”
mentioning
confidence: 99%